Public Administration as an Object of Scientific Research and a Direction of Civil Servants’ Education - A. A. Likhtin (Управленческое консультирование)
The article is devoted to systematizing and updating the research and educational characteristics of public administration. The research method is a problem analysis of the public administration research discipline and the design of the problem of training personnel for the contemporary public service. The result of the study is the justification of the need to match the key competen- cies of civil servants to the priority areas of public administration as a scientific discipline. The article concludes that contemporary public administration should be understood as a practical activity to achieve national and regional goals and objectives through state organizations and public participation. This definition allows to accumulate both domestic and foreign experience, as well as combine practice-oriented and research characteristics of the concept under study. The theoretical basis of public administration is determined by two key methodological approaches: socio-engineering that is focused on the search for optimal management models for solving prob- lems that arise in society in a way; and humanitarian, that is based on the need to overcome bureaucracy and inertia of the management system. The subject of contemporary public admin- istration consists of some problem areas, including: international, national, regional and local public administration systems; organization and implementation of sectoral and sectoral policies, strategies, projects and programs; administrative processes and procedures; research of the state and municipal service; civil society; information support and digital transformation of administration. The article substantiates that the Russian education system has now created conditions for more flexible consideration of the requests of the state and municipal service system in terms of the composition and quality of officials’ competencies. The author comes to the conclusion that the dynamics of the competence approach to the civil servants education is quite optimistic: on the one hand, educational standards and training plans flexibly take into account the needs of the state and municipal service, and on the other hand, they correspond to modern trends in the transformation of the public administration system towards a more efficient organization of interac- tion between the state and citizens.